2010
DOI: 10.1007/s10029-010-0639-2
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic linea arcuata hernia

Abstract: Hernias are often associated with congenital defects or incisional breakdown. Even though most of the linea arcuata hernias are asymptomatic, we present a rare case of a symptomatic linea arcuata hernia with associated internal herniation of the colon sigmoideum in a woman without previous abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…LAH is a rather recently described and peculiar type of interstitial parietal hernia of the AW which consists of a generally asymptomatic ascending protrusion of intraperitoneal structures under the linea arcuata (LA) or arcuate line of Douglas (1,32). In most cases this type of hernia appears fortuitously demonstrated during abdominal CT obtained for various other pathological conditions oblique muscle inclosing the rectus muscle itself (1).…”
Section: Linea Arcuata Hernia (Lah)mentioning
confidence: 99%
“…LAH is a rather recently described and peculiar type of interstitial parietal hernia of the AW which consists of a generally asymptomatic ascending protrusion of intraperitoneal structures under the linea arcuata (LA) or arcuate line of Douglas (1,32). In most cases this type of hernia appears fortuitously demonstrated during abdominal CT obtained for various other pathological conditions oblique muscle inclosing the rectus muscle itself (1).…”
Section: Linea Arcuata Hernia (Lah)mentioning
confidence: 99%
“…Review of the literature resulted in 4 previously reported symptomatic cases (Table 1). [1][2][3] Through the concave parietal fold created by the anatomic defect, ascending protrusion of intraperitoneal structures can occur. Minimal bulging of adipose tissue is classified as grade 1, whereas a grade 2 arcuate line hernia consists of an actual (although minimal) herniation of omental fat and/or intestinal loops.…”
Section: Discussionmentioning
confidence: 99%
“…Since the US examination appeared to be inconclusive, a CT scan was executed and misdiagnosed an LAH as a Spigelian hernia. The diagnosis of a left LAH has been corrected only during laparoscopy [3]. …”
Section: Discussionmentioning
confidence: 99%